Dental macrowear, diet, and anterior tooth use in Colobus polykomos and Piliocolobus badius. Issue 163 (February 2022) - Calhoun, Grace V.; Guatelli-Steinberg, Debbie; Lagan, Emma M.; McGraw, W. Scott
Abstract: Two similarly-sized colobine species living sympatrically in the Ivory Coast's Taï Forest that differ in both diet and oral processing behavior provide an opportunity to explore the strength of associations between feeding behavior and dental wear patterns. Here we test the hypothesis that vigorous processing of tough, hard Pentaclethra macrophylla pods by Colobus polykomos manifests in greater anterior tooth wear relative to that observed in Piliocolobus badius, which does not exploit this resource. We assessed levels of anterior tooth wear in a sample of 160 upper incisors and 131 lower incisors from 18 adult Colobus polykomos and 62 adult Piliocolobus badius naturally deceased individuals from Taï National Park. We operationalized tooth wear by dividing the area of exposed dentin by total occlusal crown area. To assess relative degrees of incisor wear, we regressed incisor wear against molar wear (sample = 105 upper molars, 135 lower molars) for the pooled Colobus polykomos and Piliocolobus badius wear data and compared the number of individuals from each species that fell above and below the pooled regression curve for each model using Chi-square tests of independence and odds ratios. Under our hypothesis, we would expect more Colobus polykomos points above the pooled regression curve than Piliocolobus badius, indicating higher incisor wear relative to molar wear in Colobus polykomos . Nine of sixteen interspecific comparisons demonstrated this predicted pattern; however, none of the Chi-square tests or odds ratios were significant, indicating no difference between Colobus polykomos and Piliocolobus badius incisor wear relative to molar wear. The absence of significant differences in incisor wear relative to molar wear highlights the challenge of identifying idiosyncratic feeding behavior in fossil taxa and the necessity for continued exploration of the relationship between diet and macrowear.